Assessing risk perceptions and attitude among cotton farmers: A case of Punjab province, Pakistan. (June 2016) - Iqbal, Muhammad Amjed; Ping, Qing; Abid, Muhammad; Muhammad Muslim Kazmi, Syed; Rizwan, Muhammad
Abstract: Cotton farmers have to deal with various kind of environmental and production risks. Risk attitude and perceptions play an important role in shaping farmers' decision regarding farm operations and management of exposed risks. Research on various aspects of managing risks in developing countries is few. Hence, keeping in view the research gap, this study aims to investigate the farmers' attitude and perceptions of various kinds of risks to which cotton crop is exposed in Pakistan. This study is based on a farm household survey of 480 farmers in six cotton belt districts of Punjab province, Pakistan. Equally Likely Certainty Equivalent (ELCE) and risk matrix methods are used to determine risk attitude and risk perceptions respectively. In addition, factor affecting farmers' attitude and perceptions are also analyzed by using probit model. The findings of the study revealed that that majority of farmers are risk averse in nature and reported flood, excessive rainfall, increased incidents of crop diseases and higher input prices as major risks exposed to their cotton crop. Furthermore, study found that age, education, location, off-farm income and access to market information are the factors which significantly (either positively or negatively) affect the farmers' risk perceptions and attitude. Study provides useful firsthand information to researchers and policy makers about the local understanding of risks to cotton crop in a developing country which could be used for research on farmers' adaptation to exposed risks.